Social Values Demonstrated by Secondary School Students in Selected Local Government Areas of Ekiti State, Nigeria - Oluwagbohunmi, Margaret Folu (European Scientific Journal, ESJ, 2020)
This paper focuses on determining the social values displayed by secondary school students in selected local government areas of Ekiti State. The study examined the influence of gender and location on social values exhibited by the students. Descriptive research design of the survey type was adopted with a sample of 540 students selected through multistage sampling procedure. This was done using simple and stratified random sampling techniques with one research question and two research hypotheses. A selfstructured questionnaire tagged ‘Questionnaire on Social Values’ (QSV) was the instrument used for data collection. The instrument was validated and tested for reliability. Test-retest reliability coefficients of 0.77 was obtained and found appropriate for the study. Research question was analysed descriptively using percentages, means and standard deviation while the two hypotheses were tested using t-test statistical analysis at 0.05 level of significance. Findings revealed that hard work and honesty were the most demonstrated values, while obedience and patience were the least social values demonstrated by the students. The study also showed a significant difference between social values demonstrated by male and female students and between students from rural and urban areas. Based on the findings, it was recommended among others that parents should intensify efforts to give traditional value education to their children to help them develop into morally upright and responsible adult citizens.